2019
DOI: 10.1186/s12904-019-0458-x
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care education in the undergraduate medical curricula: students’ views on the importance of, their confidence in, and knowledge of palliative care

Abstract: Background The need for palliative care is increasing. Since almost every junior doctor will come across palliative care patients, it is important to include palliative care in the undergraduate curriculum. The objective of this research is to gather undergraduate students’ views on palliative care in terms of its importance, their confidence in and knowledge of the domain. Methods Final-year medical students at four Dutch medical faculties were surveyed. The questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
1
34
0
5
Order By: Relevance
“…The majority of studies (n=4) were from the UK,19–22 with the remainder published in Germany (n=3),23–25 Australia, (n=2)26 27 USA (n=2),28 29 India (n=1),30 The Netherlands (n=1)31and New Zealand (n=1),32 with a collaborative study between the UK and USA (n=1) 33. Publication year ranged from 1993 to 2019.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies (n=4) were from the UK,19–22 with the remainder published in Germany (n=3),23–25 Australia, (n=2)26 27 USA (n=2),28 29 India (n=1),30 The Netherlands (n=1)31and New Zealand (n=1),32 with a collaborative study between the UK and USA (n=1) 33. Publication year ranged from 1993 to 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies included data pertaining to student characteristics, however, there was a lack of consistency between studies in terms of how characteristics were reported. With studies reporting gender identity characteristics (n=7), all reported a greater proportion of female participants (range 50%–74%) 21 22 25 28 29 31 33. Only five studies recorded participant age, with the the most common age range being 20–30 years old 22 25 29 31 33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students from others studies lack PC´s knowledge , especially on the pain and symptom control aspects (14). However, an integrated PC curriculum leads to improved knowledge (23) and physicians with palliative medicine education make less aggressive decisions in end-of-life care, as to withdraw lifeprolonging therapies (24).…”
Section: Symptom´s Control and Treatmentmentioning
confidence: 99%
“…This study focused on the Netherlands as one of the European countries where palliative care [9], albeit marked as general care, still receives very limited attention in medical curricula. In a previous study [10], Dutch final-year medical students reported that their curricula, indeed, did not adequately cover many of the palliative care aspects they deemed important. This finding ties in with studies from different countries showing that students lack knowledge and confidence in caring for patients requiring palliative care [11][12][13][14].…”
Section: Introductionmentioning
confidence: 96%